The Americanisation of the world trade order - Qureshi, Asif H. (Asif Hasan), 1956- (London ; New York : Routledge, 2022)
"This book provides insights into the world trading order that is informed by power in particular, the unidirectional norm imparting impact of US foreign trade law and practice on its trading partners and non-State actors. In this context, the recent tensions between the US and China have brought to the fore several fundamental and systemic questions. Underpinning these is the challenge of accommodating economic power under the rule of international economic law, including inculcating responsibility in its engagement. In the light of the recent US challenges to the world trading order"--Publisher's description.
The Americanisation of the International Economic Order and Its Normative Boundaries -- United States Special 301 Reviews of Foreign Intellectual Property Protection -- US Surveillance of Foreign Currency Exchange & Macroeconomic Practices -- A Public International Law Perspective of the US National Security Approach to Foreign Trade -- US Preferential Market Access Conditions for Developing Countries -- Exports Under the US Export Control Reform Act 2018.
Keywords: International trade; Foreign trade regulation; United States -- Commercial policy; BUSINESS & ECONOMICS / International / Economics; LAW / Commercial / International Trade